Outcomes of One-Stage Arthroscopic Ankle and Tibiotalocalcaneal Arthrodesis with External Fixation for Septic Ankle and Hindfoot Arthritis: A Case-Series Study - Ying Li MD; Wenjing Li MD (Foot & Ankle Orthopaedics)
Category: Hindfoot; Arthroscopy Introduction/Purpose: The occurrence of infection in the ankle and hindfoot presents a formidable surgical challenge. Currently, there is a lack of consensus regarding its treatment strategies. The purpose of this study is to investigate the outcomes of one-stage arthroscopic ankle and tibiotalocalcaneal (TTC) arthrodesis in the treatment of septic ankle and hindfoot arthritis. Methods: A retrospective consecutive case-series study was conducted involving 6 patients diagnosed with acute or chronic septic ankle or hindfoot arthritis, who underwent operative intervention entailing thorough debridement, arthroscopically assisted one-stage ankle or TTC fusion, and external fixation. The American Orthopaedic Foot and Ankle Society (AOFAS) ankle-hindfoot score and visual analog scale (VAS) pain score were determined preoperatively and at the final follow-up. Demographic and clinical data, inclusive of perioperative and postoperative complications, were recorded. Results: The study cohort comprised 2 males and 4 females, with a mean age of 48.7 years (range, 26-75) at the time of surgical intervention. At the final follow-up (mean, 26.5 months; range, 16-48), the AOFAS scores exhibited a significant improvement, ascending from an initial mean of 38.8 (range, 12-57) to 80.0 (range, 54-92) (P = .007). VAS scores indicated a substantial reduction in pain, decreasing from 6.5 (range, 4-9) to 0 (range, 0-5) (P = .046). All patients had achieved osseous consolidation, with an hindfoot infection control rate of 100%. Conclusion: One-stage arthroscopic ankle and TTC arthrodesis with external fixation stands as an effective therapeutic choice for septic ankle or hindfoot arthritis. This approach yields favorable outcomes characterized by effective infection control, favorable osseous consolidation, and significant functional restoration of the affected limb.